Necesidad de reformar los incisos 1 y 3 del artículo 97 del código del trabajo a fin de aumentar un valor adicional en el pago de las utilidades que perciben los trabajadores que son padres de familia a cargo de niñas, niños y adolescentes con discapacidad con observancia de los derechos de las personas y grupos de atención prioritaria reconocidos por la constitución en su artículo 35. - Sánchez Benítez, Cristian Fernando (2022)
This curricular integration research denominated "Need to reform subsections 1 and 3 of article 97 of the Labor Code in order to increase an additional value in the payment of utilities received by workers who are dependent parents of girls, boys, and adolescents with disabilities with observance of the rights of people and groups of priority attention recognized by the Constitution in its article 35”. The problem arises due to it has not been considered at the time of the distribution of the Utilities by the employer or the private company towards their workers, they pay an additional value when it comes to parents who have under their tutelage and care girls, boys, and adolescents with disabilities. The Constitution of the Republic of Ecuador and International Law recognize and guarantee the rights of workers and people with special abilities. In this way, the development of this research work is related to Utilities that workers of private companies receive, as well as it refers to priority attention groups (girls, boys, and adolescents) that will be addressed. disabled). Currently, the Labor Code determines the following: The employer or the private company distributes 15% of the Net Profits obtained throughout the previous fiscal year and divides it as follows: 10% equally to all workers and the remaining 5% in proportion to the family burden (spouse or common-law partner, children under the age of eighteen and disabled children of any age). As can be seen, paying an additional value has not been considered in the case of adolescents and children with disabilities, since their condition is double vulnerability and they also depend on the economic support of the worker. Thus, in this research work theoretical, doctrinal, and legal issues will be addressed, in addition, a methodology will be adopted that allows proposing a solution to the problem described.